International digital solidarity policies and diffusion of ICT in West Africa : progress and prospects - (:unkn) unknown (My University, 2013)
The World Summit on the Information Society (Geneva 2003 and Tunis 2005) advocated the digital solidarity as a solution to end inequalities in access to information and communication technologies (ICT) between developed and developing countries. Following the Summit, two institutional mechanisms (the World Digital Solidarity Fund and the World Digital Solidarity Agency) have been created. These institutions were designed to contribute to reducing the digital divide by promoting widespread access to ICT through international programs specifically targeting African countries. This thesis analyzes the effects of international digital solidarity policies and programs in Africa. It examines specifically the conditions for mobilizing human, financial and technological resources for the participation of African countries in the information society. It also argues that this new approach of North-South cooperation in the field of ICT does not really break with traditional technical assistance projects. The thesis also reveals gaps between the objectives announced by international policies and the actions that have been carried out in West Africa countries in bridging the digital divide.
Keywords: African Research